Lola - Libongco, John Daryl Angeles; Rownd, Robert; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines, 2017)
A young girl recollects her memories that unveil the days before the sudden death of her grandmother, only to realize that her passivity has also assisted in the events which led to the present.

Lola (Grandmother) is a film that focuses on the everyday characteristics of a typical middle-class Filipino family, but rather on the whole idea itself.

With the goal of achieving the creation of a feminist film in mind, Lola and the filmmaker himself intends to criticize how the typical household functions and how everyone, may they be male, female, or any other gender or sex, can commit sexism towards women.
Thesis (B.A. Film)
Keywords: University of the Philippines Diliman -- College of Mass Communication; Short Films -- Philippines; Grandmothers -- Philippines; Families -- Philippines; Sexism -- Philippines